2018
DOI: 10.1055/s-0037-1617443
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infections Complicating Lung Transplantation

Abstract: Lung transplantation is an increasingly utilized modality for treating advanced lung disease. However, lung transplant recipients (LTRs) experience high rates of infection-related mortality and, compared with other solid organ transplant recipients, are at increased risk of infectious complications given the intensity of immunosuppression employed, the presence of airway abnormalities after surgery and exposure of the allograft to the environment. Fungal infections, particularly mold infections, are problemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 440 publications
(743 reference statements)
1
26
0
Order By: Relevance
“…The incidence and type of fungal infections may vary depending on different transplantations and geographical regions. Invasive mold infections, particularly aspergillosis, are more common in lung transplant recipients [27]. Marjani et al [12] reported 8 (40%) cases of aspergillosis among 20 lung transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and type of fungal infections may vary depending on different transplantations and geographical regions. Invasive mold infections, particularly aspergillosis, are more common in lung transplant recipients [27]. Marjani et al [12] reported 8 (40%) cases of aspergillosis among 20 lung transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The beginning date cutoff was January 1, 2001, and the search was last updated on December 10, 2019. In addition, the bibliographies of 2 pertinent reviews 33,37 were assessed for references not identified by the aforementioned search strategy. Pertinent unpublished studies were identified from transplant conferences' meeting abstracts; authors were contacted to obtain full study details as available.…”
Section: Literature Searchmentioning
confidence: 99%
“…The transplanted organ is an important determinant in this assessment. For example, although Candida infection is the most common infection in SOT overall, infection with Aspergillus is most common in lung transplant recipients [25]. Evaluation of the PATH alliance registry in the US and Canada from 2004 -2008 demonstrated patients with liver transplantation experienced the shortest time to invasive mold infections and had the highest rate of dissemination [19].…”
Section: Figure 1 Drivers Of Pre-test Probability For Invasive Fungal Infections In Solid Organmentioning
confidence: 99%